2015
DOI: 10.1186/s13567-015-0143-x
|View full text |Cite
|
Sign up to set email alerts
|

Grazing livestock are exposed to terrestrial cyanobacteria

Abstract: While toxins from aquatic cyanobacteria are a well-recognised cause of disease in birds and animals, exposure of grazing livestock to terrestrial cyanobacteria has not been described. This study identified terrestrial cyanobacteria, predominantly Phormidium spp., in the biofilm of plants from most livestock fields investigated. Lower numbers of other cyanobacteria, microalgae and fungi were present on many plants. Cyanobacterial 16S rDNA, predominantly from Phormidium spp., was detected in all samples tested, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…The DAB (also named DABA) is a component of some bacteria wall (e.g., genus Corynebacterium ) [ 70 ] or actinomycetes (e.g., Agrococcus jenensis ) [ 71 ]. The presence of DAB has been also specifically reported in angiosperm species such as Lathyrus latifolius or Brassica oleracea [ 19 , 28 ] as well as in aquatic [ 32 ] or terrestrial [ 72 ] plants. DAB was reported for the first time in 2008 in the cyanobacteria Calothrix sp.…”
Section: Discussionmentioning
confidence: 98%
“…The DAB (also named DABA) is a component of some bacteria wall (e.g., genus Corynebacterium ) [ 70 ] or actinomycetes (e.g., Agrococcus jenensis ) [ 71 ]. The presence of DAB has been also specifically reported in angiosperm species such as Lathyrus latifolius or Brassica oleracea [ 19 , 28 ] as well as in aquatic [ 32 ] or terrestrial [ 72 ] plants. DAB was reported for the first time in 2008 in the cyanobacteria Calothrix sp.…”
Section: Discussionmentioning
confidence: 98%
“…Recent evidence from whole-genome sequencing confirmed that Melainabacteria constitute a class within the Cyanobacteria phylum because the two groups share common ancestral traits, such as the cell envelope structure and the presence of putative circadian rhythms (54). Taxa within this group have been detected in various environments, including groundwater, drinking water and wastewater treatment plants (54,55), terrestrial plants, and animal guts (56). To our knowledge, their presence has not been previously reported in lakes.…”
Section: Discussionmentioning
confidence: 87%
“…Studies are warranted to determine whether breastfed infants may be exposed to BMAA via mothers' milk. Likewise, as cyanobacteria may be present in fields used for livestock grazing or fed to livestock directly (Šimkus et al, 2007, Kulpys et al, 2009, Christaki et al, 2012, McGorum et al, 2015, concentrations of BMAA should be determined in cows' milk.…”
Section: Discussionmentioning
confidence: 99%
“…BMAA is a non-protein amino acid produced by cyanobacteria, dinoflagellates and diatoms (Cox et al, 2005, Jiang et al, 2014a and detected in aquatic organisms, including sharks and bony fish, crustaceans and mussels that are consumed by humans (Brand et al, 2010, Jonasson et al, 2010, Mondo et al, 2012, Field et al, 2013, Masseret et al, 2013, Banack et al, 2014, Jiang et al, 2014b, Lage et al, 2014, Banack et al, 2015, Lage et al, 2015, Reveillon et al, 2015. BMAA has also been reported to be present in brains of Alzheimer's disease patients and ALS patients (Murch et al, 2004b), a finding that was replicated by an independent team using the same techniques (Pablo et al, 2009), while another team using different techniques failed to detect BMAA (Snyder et al, 2009).…”
Section: Introductionmentioning
confidence: 98%